Argyrophilic Nucleolar Organizer Regions in Premalignant and Malignant Oral Lesion: A Quantitative and Qualitative Assessment - Shafali Singh; Seema Sharma; Manu Gupta; Akansha Singh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Argyrophilic nucleolar organizer regions (AgNORs) has been considered to be useful indiagnostic pathology, mainly to distinguish benign lesions from their malignant counterparts.Aim: This study was done to evaluate the significance of various AgNOR parameters in differentiatingpremalignant and malignant oral lesions.Materials and Methods: The study was performed on thirty five archival tissues consisting of samplecomprised of five normal mucosa, fifteen premalignant lesions and fifteen malignant oral lesions. AgNORswere assessed both quantitatively and qualitatively. The data were analyzed using ANOVA and Chi squaretest.Results: Quantitatively and qualitatively significant difference was noticed. Quantitatively significantdifference in the mean value of AgNORs noticed between the premalignant and malignant lesions. In termsof qualitatively, the premalignant and malignant oral lesions differed significantly from normal mucosa.Conclusion: To conclude, the AgNOR count is the most appropriate marker to differentiate betweenpremalignant and malignant oral lesions.